Analisis Cacat Pengelasan SMAW pada Baja AISI 1040 dengan Metode Bending Test - Ibnu Hafiz Wardhana; Zainal Abadi; Waskito Waskito; yahril yahril (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the quality of AISI 1040 medium carbon steel welds using the Shielded Metal Arc Welding (SMAW) method with a V-groove through bending tests. The tests were conducted to assess the weld's ability to withstand plastic deformation due to bending loads and the effect of defects on weld integrity. The testing procedure refers to the ASTM E290 and AWS D1.1 standards. Of the seven specimens tested, four of them—Face 3, Root 1, Root 2, and Root 3—passed the test without defects, indicating good fusion between the weld metal and the base metal. Meanwhile, Face 1, Face 2, and Face 4 experienced small cracks in the Heat Affected Zone (HAZ) due to undercut and slag inclusion. The Root 1 specimen recorded the highest maximum load of 16,343.46 N. Overall, the SMAW weld joint with a V groove on AISI 1040 steel showed good flexural strength and met structural feasibility standards.